Surface Integrity and Friction Performance of Brass H62 Textured by One-Dimensional Ultrasonic Vibration-Assisted Turning - Xianfu Liu (MDPI AG, 2021)
The processing method, one-dimensional ultrasonic vibration-assisted turning (1D UVAT), is a potential and efficient way for fabricating a micro-textured surface. This paper aims at exploring the surface integrity and friction performance of brass H62 textured by the 1D UVAT. Four micro-textured surfaces with a specific distribution, size, and shape of dimples were fabricated by optimizing processing parameters, and the corresponding surface topography, subsurface microstructure, and surface roughness were observed and analyzed. A series of friction tests were carried out under oil-lubricating conditions to research the friction performance of micro-textured surfaces. The results show that the reason for the deviation between theoretical and experimental values of dimple depth was further revealed by observing the corresponding subsurface microstructure. The surface roughness of the micro-textured surfaces prepared is related to the number of micro-dimples per unit area and dimple size, which is greater than the surface generated by conventional turning. Compared with the polished surface and micro-grooved surface, the micro-textured surfaces have better friction performance with a lower frictional coefficient (COF) and wear degree. For the micro-textured surface fabricated by 1D UVAT, the number of micro-dimples per unit area has a great effect on the friction performance, and choosing a larger number is more conducive to improving the friction performance under the oil-lubricating condition. Consequently, this study proves that the proposed 1D UVAT can be a feasible candidate for preparing a micro-textured surface with better tribological property